2018
DOI: 10.3390/coatings8090318
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Edible Coating Based on Chitosan and Oxidized Starch on Shelf Life of Carica papaya L., and Its Physicochemical and Antimicrobial Properties

Abstract: Papaya production plays an important economic role in Mexico’s economy. After harvest, it continues to ripen, leading to softening, skin color changes, development of strong aroma, and microbial spoilage. The objective of this work was to apply an active coating of chitosan–starch to increase papaya shelf life and to evaluate physicochemical and antimicrobial properties of the coating. Papaya surfaces were coated with a chitosan-oxidized starch (1:3 w/w) solution and stored at room temperature (25 ± 1 °C) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 44 publications
2
14
0
1
Order By: Relevance
“…TA content is regarded as an important indicator of respiration rate of fruits as organic acids are substrates for the respiratory metabolim [49]. As shown in Figure 1g, the TA content of coated and uncoated papayas decreased as the storage period was extended, as previously reported by others [49].…”
Section: Titratable Aciditysupporting
confidence: 76%
“…TA content is regarded as an important indicator of respiration rate of fruits as organic acids are substrates for the respiratory metabolim [49]. As shown in Figure 1g, the TA content of coated and uncoated papayas decreased as the storage period was extended, as previously reported by others [49].…”
Section: Titratable Aciditysupporting
confidence: 76%
“…The cationic nature of the polymer allows it to bind to different chemicals species, ranging from organic macromolecules to metal nanoparticles [12][13][14]. Natural oils or extracts of natural products can be incorporated into the chitosan matrix, for example, by cross-linking, producing solutions, films or beads [15][16][17]. In the particular case of propolis, its polyphenols have been reported to form hydrogen bonds and covalent bonds with the functional groups in chitosan [18].…”
mentioning
confidence: 99%
“…Hazarika, Lalthanpuii and Mandal (2017) also reported reduced firmness of coated papaya fruits with increased shelf life. Escamilla-García et al (2018) reported that uncoated papaya fruits had a firmness loss of 92% during storage, while those coated with chitosan and oxidized starch had a firmness reduction of only 47%. The valor similar values to the present work, where at the end of 8 days the fruits presented 43% less firmness.…”
Section: Resultsmentioning
confidence: 99%